PENGARUH CAR, FDR, NPF, DAN BOPO TERHADAP ROE BANK SYARIAH MANDIRI PERIODE DESEMBER 2008-AGUSTUS 2012 - Thyas Rafelia; Moh. Didik Ardiyanto (Diponegoro Journal of Accounting, 2013)
The research aimed to examine the effect of Adequancy Capital Ratio (CAR), Financing to DepositRatio (FDR), Non Performing Financing (NPF), and Operating Expenses to Operating Income(OEOI) for profitability of Mandiri Islamic Bank. Profitability measurement tools used wereReturn on Equity (ROE). Mandiri Syariah Bank (BSM) was taken as sample for This research.The data used for this research were obtained from the data of Monthly Published FinancialReport Period December 2008 up to August 2012. The analysis technique used is linear regressionthat aims for estimating the relationships among variables. The results of this research indicatethat CAR, FDR, NPF, and OEOI influentials to ROE. There are two variables that significantlypositive effect on ROE, FDR and NPF. The other variable have a significant negative effect isOEOI, while CAR negative but not significant effect on ROE